INDONESIA DIGITAL GOVERNMENT AUDITING MODEL USING RULE BASED AND CLOUD CASE-BASED REASONING - Hari Setiabudi Husni; Arief Ramadhan; Edi Abdurachman; Agung Trisetyarso (Asosiasi Dosen Muda Indonesia, 2022)
This paper explores the possibility of combining process model of Digital Government auditing, Rule Based and Cloud Case-Based Reasoning. Digital Government and Digital Government Auditing definition retrieve from Indonesia Presidential Regulation number 95-year 2018. consist two goals that the regulation aims, the first was to realize good governance clean, effective, transparent, and accountable as well as quality and reliable public services an digital government system is required; and second was to improve cohesiveness and efficiency of the electronic-based government system governance and management required national digital government; The existence variation of regulations and auditing standard creating complex reference database and hard to find solution for assessment and auditing Indonesia Digital Government. Rule-based and Case-based reasoning could help auditor in searching and documenting unsolved and solved auditing problem. The result shown that there is possibility to enhance audit process to create better audit result and more efficient in audit working time.